Remoção de melanoidinas aplicando carvão ativado produzido a partir de torta de nabo forrageiro carbonizado em forno de micro-ondas - Diego Luiz Nunes (2013)
The removal of melanoidins from aqueous solutions is the objective of this work. The molecules, also called Maillard Reaction Products, were synthesized and characterized in a glucoseglycine system. The chemical stability and size distribution of the molecules were confirmed. The adsorption process with activated charcoal is commonly applied for the removal of melanoidins. Four different sorbents were carbonized in a microwave oven, using the Raphanus sativus press cake, an agricultural residue, as the precursor. The materials were individually processed after washing or after manual mixing with concentrated chemical agents, such as nitric acid, phosphoric acid and potassium hydroxide in a 1:1 mass ratio. All the sorbents were evaluated for efficiency of production, and their physical and chemical characteristics such as surface area, organic groups and the structural modifications that result from chemical and thermal processes were studied. All the activated charcoals had a minimum surface area and low porosity, which is desirable to avoid capillary effects in the adsorption mechanism evaluation. The impregnation by chemical groups was confirmed by the effects on the thermal degradation process, FTIR and the pHPZC values. Adsorption experiments were performed for each sorbent previously organized by DOE. The quadratic model obtained was able to describe the influence of dose and the initial pH of the solution on the adsorbent. The influence of initial melanoidin concentration and the contact time were extensively discussed with the application of several classical equations, calculated by nonlinear regression methods. The adsorption by acid-treated charcoal could be described by the Langmuir model and presented a homogenous process and monolayer adsorption profile. For the directly carbonized material and the base-treated charcoal, the Freundlich model showed a better fit. For all the chemically treated materials, an increase in adsorption capacity and a favorable process was observed when evaluating the Langmuir model parameters. The low correlation values for the DR isotherm model corroborate the hypothesis of minimal porosity of the materials. The pseudo-second order kinetic model fitted best for all the sorbents. This fact could be allied to the possibility of a chemisorption process. The diffusion coefficients and adsorption rates presented a preferential adsorption for small molecules because of the profile observed when increasing the initial melanoidin concentration. Phenolic and amino groups and/or aromatic rings from melanoidin molecules are capable of interacting with the adsorbent surface via hydrogen bonds and - electronic forces. The Temkin model also returned good correlation values. This fact could increase the possibility of lateral interactions with the adsorbed molecules, justifying the adsorption capacity in the experiments. The thermodynamic analysis showed that the melanoidin adsorption is a spontaneous, favorable and exothermic process.